Mechanisms of Lipid Modulation and Agonist Activation in the Muscle Nicotinic Acetylcholine Receptor - Thompson, Mackenzie (Université d'Ottawa / University of Ottawa, 2024)
The muscle nicotinic acetylcholine receptor (nAChR) is a synaptic receptor that mediates neuromuscular communication by allowing cations to flow into a skeletal muscle cell in response to acetylcholine (ACh) binding. ACh binding transiently converts the nAChR from a non-conductive resting state to a conductive open state, increasing the intracellular voltage, ultimately leading to muscle contraction. The composition of the surrounding lipid environment also influences the stabilities of these, and other, conformational states to modulate nAChR function. While there is a reasonable understanding of what conformational states agonists and lipids stabilize to exert their effects, the mechanisms by which they do so remain enigmatic. In this thesis, the structural mechanisms of agonist activation and lipid modulation are explored using a combination of screening mutagenesis and electrophysiology. In manuscripts 1 and 2 extensive functional characterization of the peripheral M4 α-helices in the nAChR transmembrane domain (TMD) is used to explore different potential pathways of lipid modulation. Lipid modulation is suggested to occur through unique and independent mechanisms in each nAChR subunit that add together to account for the dramatic effects of lipids on nAChR function. In manuscript 3 new nAChR structures in apo and agonist bound states are used to guide a functional characterization of the interface between the extracellular domain (ECD) and the TMD, which is responsible for coupling agonist binding to channel gating. The new structures, which contradict previously reported mechanisms of nAChR activation, highlight conformational asymmetry at the ECD - TMD interface in α versus non-α subunits. We propose that agonist binding allows local "tension" at the ECD - TMD interfaces of the α subunits to "relax" to a conformationally symmetric active state. The results of these studies enhance our understanding of the mechanisms that underly allosteric transitions in the nAChR.
Keywords: Biophysics; Electrophysiology; Cryo-EM; nAChR; Lipid modulation; Activation